(untitled) (The Review of Diabetic Studies, 2025)
Health informatics is an emerging discipline that is essential for the coordination of intricate healthcare services and is crucial for ensuring the security of healthcare within countries. This paper will discuss the role of health informatics in the coordination of nursing, lab, and epidemiology services based on analysis of the current capabilities of the human resource in these services, technology adoption, and challenges of coordination. From current literature in the development of a health informatics public health practitioner workforce, the adoption of electronic medical records, and health informatics education, this review underscores the essential determinants of success in the coordination of these services, including human resource skills, data security, documentation quality, and integration. Findings of this review show that, despite the very low levels of health informatics practitioners as an estimation of 1.1% of the healthcare professional population working within state health services and 0.2%—0.5% within equivalent local health services, their role is paramount in linking the two domains of clinical and public health practice. Much is still needed in terms of health informatics education within nursing, lab, and epidemiology, and this is for the optimal coordination of these practices.